Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 Pada Materi Limit Dengan Model Pembelajaran Discovery Learning Di SMK N 1 Adiwerna Kabupaten Tegal - Saraswati Sri Hastanti (Universitas Pancasakti Tegal, 2022)
This study aims to describe three tenth grade SMK N 1 Adiwerna plans implementation learning those contain limit material with different learning models. . This study use the comparative descriptive qualitative research methods. The results of the analysis show the components of the learning implementation plan made by the teacher are guided by the Circular of the Ministry of Education and Culture Number 22 of 2016 Contain learning objectives, learning activities and evaluations. There are 7 learning objectives that meet the criteria according to basic competencies and in accordance with the A.B.C.D method and 3 learning objectives those contain HOTS unsure. In the 1st plan implementation learning that uses discovery learning there ara 13 of 43 activities those show the characteristics of 21st innovative learning. In the 2nd plan implementation learning that uses problem based learning (PBL) there ara 10 of 35 activities those show the characteristics of 21st innovative learning. In the 3rd plan implementation learning that uses online learning there ara 3 of 18 activities those show the characteristics of 21st innovative learning.